Політичний аспект російсько-українських відносин 20-х років ХХ ст. у новітній історіографії - Сокирська, В.В. (Історичний архів. Наукові студії, 2013)
Досліджено історіографічний доробок українських, російських та зарубіжних вчених
щодо політичного підґрунтя російсько-українських відносин 20-х років ХХ століття,
звернуто увагу на його проблемно-тематичне розмаїття та пріоритетні напрямки
дослідження. Простежено специфіку й особливості дослідження зазначеної тематики.
Доведено, що новітній період історіографії позначився підвищенням інтересу до історії
становлення російсько-українських відносин після розпаду Російської імперії та
створення і становлення СРСР. За останні два десятиріччя у вітчизняній і зарубіжній
науковій літературі зроблено значний поступ у справі зваженого й об’єктивного аналізу
російсько-українських відносин окресленого періоду. Исследовано историографическое наследие украинских, российских и зарубежных
ученых относительно политической основы российско-украинских отношений 20-х
годов ХХ века, обращено внимание на его проблемно-тематическое разнообразие и
приоритетные направления исследования. Прослежена специфика и особенности
исследования указанной тематики. Доказано, что новейший период историографии
характеризуется повышением интереса к истории становления российско-украинских
отношений после распада Российской империи, создания и становления СССР. За
последние два десятилетия в отечественной и зарубежной научной литературе
сделан значительный прогресс в деле взвешенного и объективного анализа российско-
украинских отношений очерченного периода. Topic of scientific exploration involves the study of Russian-Ukrainian relations, but in the
context of the historiography of the problem. It is proved that the latest period historiography
marked increase in interest in the history of the development of Russian-Ukrainian relations
after the collapse of the Russian Empire and the creation and development of the USSR. Over
the past two decades in domestic and foreign scientific literature made considerable progress in
the case of a balanced and objective analysis of the Russian-Ukrainian relations mentioned
period. Overcoming stereotypes of the Soviet era, the current moderate Ukrainian and Russian
historiography searching scientific coverage of Ukrainian-Russian relations, gradually releasing
from ideological and politicized layers. Summing historiographical analysis of contemporary
foreign literature on the abovementioned problem it should be noted the growing number and
diversity of ideas and conceptual interpretations. And despite much literature in which authors in
varying degrees, affect the problem of Russian-Ukrainian relations in Ukraine of the 1920s,
special work on the subject available. This suggests that the problem is the political aspect of
Russian-Ukrainian relations requires further in-depth research.